Speolabeo, a new genus name for the cave fish Bangana musaei (Teleostei: Cyprinidae) - Kottelat, Maurice (Zootaxa, 2017)
Speolabeo, new genus, is established for Bangana musaei, a fish from caves in the Khammouan Karst in Laos. It was originally tentatively placed in the genus Bangana s.l. Besides characters related to hypogean life (absence of eyes, absence of pigment resulting in a whitish body), it is distinguished from all species of Bangana s.l. in having only 7–8½ branched dorsal-fin rays, the pelvic-fin at the vertical between the first unbranched and first branched dorsal-fin rays, and details of mouth morphology.